Twinned LaAlO3 substrate effect on epitaxially grown La-Ca-Mn-O thin film crystalline structure - Song, JH; Kim, KK; Oh, YJ; Jung, HJ; Song, JH; Choi, DK; Choi, WK (ELSEVIER SCIENCE BV, 2001)
La-Ca-Mn-O (LCMO) thin film was epitaxially grown on LaAlO3 (1 0 0) substrate using RF magnetron sputtering. The epitaxial relationship between LCMO and LaAlO3 (LAO), was characterized using MeV He-4(2+) backscattering (BS)/channeling and a 4-circle X-ray diffractometer (XRD). The LCMO film deposited at 600 degreesC with an RF power of 100 W showed the channeling minimum yield of 4.98% indicating its excellent crystallinity and high c-axis orientation. Through channeling angular scan measurement, it is confirmed that the 145 nm thick LCMO thin film conserved the compressive stress. The FWHM value of LCMO (2 0 0) peak in XRD theta -rocking is mainly influenced by the twin structure of LAO substrate. It is also interesting that the twin angle of LAO substrate, 0.18 degrees, is very close to the separation of two peaks, 0.20 degrees, in XRD theta -rocking scan on LCMO (2 0 0) peak. From these results, it is suggested that these two subpeaks in XRD theta -20 curve were originated from each twinned plane rather than coexistence of strained and relaxed layers. In addition, the FWHM of LCMO (2 0 0) peak obtained from high-resolution XRD D-rocking, 0.147 degrees, is smaller than any value ever reported. (C) 2001 Published by Elsevier Science B.V.
Keywords: 3-DIMENSIONAL STRAIN STATES; MOLECULAR-BEAM EPITAXY; LARGE MAGNETORESISTANCE; LA0.67CA0.33MNO3; LA0.7CA0.3MNO3; DEPENDENCE; TRANSPORT